Haematological and Biochemical Changes in Japanese Quails Coturnix coturnix Japonica and Chickens Due to Ascaridia galli Infection - Deka, K.; Borah, J. (International Journal of Poultry Science, 2008)
A study was carried out in Japanese quails Coturnix coturnix japonica and chickens (Rhode Island Red) for comparative haematological and biochemical changes occurring due to Ascaridia galli infection. Quails as well as chickens were divided into four small groups, each consisting six numbers of birds in each group and were marked as q1, q2, q3, qC and p1, p2, p3, pC, respectively. Haematological study showed that the total erythrocytic count (TEC), packed cell volume (PCV) and haemoglobin (Hb) percentage decreased significantly in infected groups of quails and chickens. The total leucocytic count (TLC) showed significant increase in infected groups of quails and chickens. Heterophils and eosinophils were increased significantly in all the infected groups of quails and chickens. Lymphocytes decreased significantly in all the infected groups. Biochemical study showed that total serum protein decreased significantly in the infected groups of quails and chickens. Serum albumin level was significantly lower in all the infected groups of quails and chickens. Serum globulin and albumin: globulin (A:G) ratio failed to show any significant difference between control and infected groups of quails and chickens.